Lithium metal oxides (metal = manganese, chromium, cobalt, or aluminium) as cathode in lithium ion batery - Rahman, Mohd. Mokhlesur (2006)
Spinel LiMn2O4 (CA-EG mixture assisted), LiMn2O4 (CA assisted), LiMn2O4 (PA assisted), Cr-doped LiCrxMn2-xO4 and layered LiCo0.7Al0.3O2 (CA and PA assisted) cathode materials have been synthesized by a sol-gel method using organic acid as a chelating agent. This technique offers better homogeneity, preferred surface morphology, reduced heat treatment conditions, sub-micron sized particles and better crystallinity. The dependence of the physiochemical properties of the powder materials on the various calcination temperatures and organic acid quantity have been extensively studied. Electrochemical behaviors of the prepared powder materials were analyzed using galvanostatic charge-discharge cycling studies in the voltage range 3.0-4.3 V (vs. Li metal) using 1 M LiPF6-EC/DMC as electrolyte. Materials LiMn2O4 (CA-EG mixture assisted), LiMn2O4 (CA assisted), LiMn2O4 (PA assisted), Cr-doped LiCrxMn2-xO4, LiCo0.7Al0.3O2 (CA assisted) and LiCo0.7Al0.3O2 (PA assisted) delivered initial discharge capacity of 29.66, 20.94, 41.65, 49.50, 97.34 and 74.43 mA h/g with the capacity retention of 71.4, 93.7, 90.6 , 91.6, 90.8 and 98.4 % of its initial capacity over only 3rd cycle, respectively. Coulombic efficiency for the materials of LiMn2O4 (CA-EG mixture assisted), LiMn2O4 (CA assisted), LiMn2O4 (PA assisted), Cr-doped LiCrxMn2-xO4, LiCo0.7Al0.3O2 (CA assisted) and LiCo0.7Al0.3O2 (PA assisted) were found to be 96.2, 89.18, 74.8, 97.6, 92.8 and 94.7 % after only three cycles, respectively. Electrochemical evaluation shows that LiCo0.7Al0.3O2 (CA assisted) materials exhibit higher initial discharge capacity whereas LiCo0.7Al0.3O2 (PA assisted) materials exhibit a better capacity retention and good coulombic efficiency